1998
DOI: 10.1164/ajrccm.158.6.9706054
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Enhances Cellular Proliferation and Inositol 1,4,5-Triphosphate Generation in Fibroblasts from Bovine Pulmonary Artery But Not from Mesenteric Artery

Abstract: When pulmonary hypertension occurs in the face of hypoxia there is remodeling of all three layers of the pulmonary vessels, but in particular, there is an increase in number of adventitial fibroblasts. Hypoxia causes vasoconstriction in the pulmonary circulation and vasodilation in the systemic circulation. We hypothesized that there are fundamental differences in oxygen sensing and cell signaling between systemic and pulmonary artery cells in response to hypoxia. Here, we determined the effect of hypoxia eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 14 publications
3
23
0
Order By: Relevance
“…However, a few reports have suggested positive roles for this kinase in promoting cell hypertrophy (39), ischemic preconditioning (40), and hemopoietic (41) and T cell proliferation or differentiation (42,43). Our results with the widely used pyr- idinyl imidazole inhibitor of p38, SB202190, demonstrating attenuation of hypoxia-induced proliferative responses of neonatal PA fibroblasts are consistent with previous reports of the role of p38 MAP kinase in the hypoxia-induced proliferative response of adult PA fibroblasts and mesangial cells (14,29). The fact that the same dose of SB202190 that attenuated hypoxia-induced proliferation augmented serum-induced proliferation also suggests potentially unique roles for p38 isozymes in hypoxic cell responses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, a few reports have suggested positive roles for this kinase in promoting cell hypertrophy (39), ischemic preconditioning (40), and hemopoietic (41) and T cell proliferation or differentiation (42,43). Our results with the widely used pyr- idinyl imidazole inhibitor of p38, SB202190, demonstrating attenuation of hypoxia-induced proliferative responses of neonatal PA fibroblasts are consistent with previous reports of the role of p38 MAP kinase in the hypoxia-induced proliferative response of adult PA fibroblasts and mesangial cells (14,29). The fact that the same dose of SB202190 that attenuated hypoxia-induced proliferation augmented serum-induced proliferation also suggests potentially unique roles for p38 isozymes in hypoxic cell responses.…”
Section: Discussionsupporting
confidence: 92%
“…However, the physiological end point of hypoxia-induced activation of MAP kinases in these cells was not examined. It has been reported that hypoxia activates JNK and p38 MAP kinase and stimulates proliferation in adult bovine PA adventitial fibroblasts (12,29). Interestingly, in these cells hypoxia has little effect on ERK.…”
Section: Discussionmentioning
confidence: 93%
“…We and others have documented that aggregate populations of fibroblasts from the PA demonstrate increased DNA synthesis under hypoxic conditions (7,8,44,50). Similar findings have been reported in aggregate populations of fibroblasts from skin and gingiva (1,5,32,44,47).…”
Section: Discussionsupporting
confidence: 82%
“…The suggestion that VEGFR-2-independent pathways cause severe PH (54) led us to explore other activities contributing to the attenuated PH phenotype. Previous reports have demonstrated increased SMC proliferation to hypoxia both in vivo and in vitro via the protein kinase C (PKC)/MAPK pathway (24,31,60,61). In this study, compared with the hypoxia-alone group the combined hypoxia/ SU-5416 group had higher levels of phosphorylated MEK1/2 and ERK.…”
Section: Discussionmentioning
confidence: 46%